Pengaruh Pemberian Rebusan Daun Kelor Terhadap Peningkatan Kadar HB Pada Ibu Hamil Trimester II Dengan Anemia Ringan Di Puskesmas Oelolok Tahun 2025 - Fitriyaningsih, Fitriyaningsih; Justian, Dini; Bauk, Kristiani (Universitas Pahlawan Tuanku Tambusai, 2025)
Anemia is a condition when the number of red blood cells in the body is lower than normal. One group of individuals who are susceptible to anemia are pregnant women because they need more iron to support the development of the fetus in the womb. WHO, anemia in pregnancy is confirmed if the hemoglobin (Hb) level is <11 g/dL.Meanwhile, the center of disease control and prevention defines anemia as a condition with Hb levels <11 g/dL in the first and third trimesters, Hb <10.5 g/dL in the second trimester, and <10 g/dL after delivery (Ahmed et al., 2023). This study aims to determine the effect of giving boiled moringa leaves on increasing HB levels in pregnant women in the second trimester with mild anemia at the Oelolok Health Center. This research method is Quasi Experiment with One group pretest and posttest design. Samples were taken using total sampling. The number of samples was 14 pregnant women. Data analysis using the Wilcoxon test. The results of the study showed P = 0.001 (P <0.05). In conclusion, there is an effect of giving boiled moringa leaves on increasing HB levels in pregnant women in the second trimester with mild anemia. It is expected that pregnant women who experience anemia or low hemoglobin levels can consume foods containing iron, especially boiled moringa leaves. Keywords: Boiled Moringa Leaves, hemoglobin levels, pregnant women